2021
DOI: 10.1177/0972150921995476
|View full text |Cite
|
Sign up to set email alerts
|

Return and Volatility Spillovers Among the Thematic Indices in India

Abstract: The article attempts to explore the interlinkages among the Nifty thematic indices and their portfolio implications. First, we examine the return and volatility spillovers among eight Nifty thematic indices, namely Energy, Infrastructure, MNC, PSE, Services Sector, Aditya Birla Group, Mahindra Group and Tata group using the vector autoregressive (VAR (1)) asymmetric BEKK–GARCH model for the period 4 January 2010–28 March 2020. Second, the estimation results are used to calculate and analyse the optimal portfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Marzuki and Newell (2021a) and Marzuki and Newell (2021b) used a unique data set of both listed and unlisted infrastructure to examine its portfolio diversification potential to find significant results in favor of infrastructure. Apart from this, two recent studies based on Indian data, Hasnat (2021) and Majumder (2021), found no significant evidence of stable cash flows by infrastructure investments. Similarly, Bianchi et al (2014) explored the separate asset class status of listed infrastructure in the USA and concluded against it.…”
Section: Introductionmentioning
confidence: 76%
“…Marzuki and Newell (2021a) and Marzuki and Newell (2021b) used a unique data set of both listed and unlisted infrastructure to examine its portfolio diversification potential to find significant results in favor of infrastructure. Apart from this, two recent studies based on Indian data, Hasnat (2021) and Majumder (2021), found no significant evidence of stable cash flows by infrastructure investments. Similarly, Bianchi et al (2014) explored the separate asset class status of listed infrastructure in the USA and concluded against it.…”
Section: Introductionmentioning
confidence: 76%
“…Numerous recent studies focus on the risk-return profiles of infrastructure and their overall benefits in the investment context (Marzuki et al, 2020). Their performance has been explored not only in the United States (Newell & Peng, 2008), but also in multiple countries, such as Australia (Newell et al, 2011), China (Newell et al, 2009), India (Hasnat, 2021;Majumder, 2021;Singhal et al, 2011), the United Kingdom (Oyedele et al, 2013), or Jordan (Gharaibeh, 2019). Most studies indicate that they offer higher profits and less risk than most liquid asset classes, such as stocks or bonds, but may be outperformed by, for example, private equity (Inderst, 2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Two recent studies examine the performance of infrastructure using listed Indian data. While Hasnat ( 2021 ) uses a composite Nifty infra index, Majumder ( 2021 ) uses eight different Nifty thematic indices including energy and infrastructure. Based on standard CAPM and M-GARCH, Hasnat ( 2021 ) finds lower returns and lower volatility for Nifty infra as compared to Nifty 50.…”
Section: Reporting the Findingsmentioning
confidence: 99%
“…No evidence of stable and resilient cash flows is found particularly for smaller firms. Majumder ( 2021 ) find significant return and volatility spillover effects of infrastructure and energy on other thematic sectors. Another Indian study (Singhal et al 2011 ) finds strong risk-adjusted performance of Indian infrastructure relative to global infrastructure, Asia-Pacific infrastructure, global stocks and Indian stocks.…”
Section: Reporting the Findingsmentioning
confidence: 99%